Matrix metalloproteinase-1 (MMP-1) rs1799750 polymorphism is associated with nasopharyngeal carcinoma (NPC) risk - Cao, L.; Li, P.; Dong, L. (Cellular and Molecular Biology, 2017)
A few studies suggested that matrix metalloproteinase 1 (MMP-1) rs1799750 polymorphism was associated with nasopharyngeal carcinoma (NPC) risk. However, other studies did not confirm this result. Thus, we did this meta-analysis to evaluate the association between MMP-1 rs1799750 polymorphism and NPC risk. We searched PubMed and EMBASE. Five studies with 1497 cases and 1643 controls were included in this meta-analysis. Subjects with MMP-1 rs1799750 polymorphism had an decreased NPC risk (OR = 0.79; 95%CI, 0.69–0.91; P = 0.0007; I2 = 70%). In the subgroup analysis by smoking, a marginally significant association was found in non-smokers (OR = 0.73, 95% CI 0.52 – 1.04, P = 0.08; I2 = 0%) but not smokers (OR = 0.59, 95% CI 0.24 – 1.42, P = 0.24; I2 = 83%). In conclusion, this meta-analysis showed that MMP-1 rs1799750 polymorphism was significantly associated with NPC risk.